(untitled) (Novateur Publications, 2023)
This study was to find emperic data on the pattern of relationship between the level of physical freshness and nutritional status with the learning achievement of MTs students in the city of Manado. Survey research method with descriptive and associative approach. The population is all MTs students in Manado City who carry out Penjas learning activities in 5 MTs. Based on the calculation of the sample size, the number of samples obtained is (n) = 30.3158 (rounded up the sample size to 75 students). Sampling technique with "simple random sampling". To measure the variable level of physical freshness "12-minute running test" Cooper method. For nutritional status variables with the "Anthropometry test" the formula "Body Mass Index (IMB)" To measure the variable of student learning achievement, the report card value of the Penjas. Analysis with statistical descriptive and associative tests, namely single and multiple correlation tests. Results obtained (1) There is a positive relationship between the level of physical freshness and learning achievement in MTs students in Manado City. (2) There is a positive relationship between nutritional status and learning achievement in MTs students in Manado City. (3) There is a positive relationship between the level of physical freshness and nutritional status together with learning achievement in MTs students in Manado City.